Identification of key genes and pathways in diabetic nephropathy by bioinformatics analysis. Issue 4 (21st January 2019) - Geng, Xiao‐dong; Wang, Wei‐wei; Feng, Zhe; Liu, Ran; Cheng, Xiao‐long; Shen, Wan‐jun; Dong, Zhe‐yi; Cai, Guang‐yan; Chen, Xiang‐mei; Hong, Quan; Wu, Di
Abstract: Aims/Introduction: The aim of the present study was to identify candidate differentially expressed genes (DEGs) and pathways using bioinformatics analysis, and to improve our understanding of the cause and potential molecular events of diabetic nephropathy. Materials and Methods: Two cohort profile datasets (GSE30528 and GSE33744) were integrated and used for deep analysis. We sorted DEGs and analyzed differential pathway enrichment. DEG‐associated ingenuity pathway analysis was carried out. The screened gene expression feature was verified in the db / db mouse kidney cortex. Then, rat mesangial cells cultured with high‐concentration glucose were used for verification. The target genes of transcriptional factor E26 transformation‐specific‐1 (ETS1) were predicted with online tools and validated using chromatin immunoprecipitation assay quantitative polymerase chain reaction. Results: The two GSE datasets identified 89 shared DEGs; 51 were upregulated; and 38 were downregulated. Most of the DEGs were significantly enriched in cell adhesion, the plasma membrane, the extracellular matrix and the extracellular region. Quantitative reverse transcription polymerase chain reaction analysis validated the upregulated expression of Itgb2, Cd44, Sell, Fn1, Tgfbi and Il7r, and the downregulated expression of Igfbp2 and Cd55 in the db / db mouse kidney cortex. Chromatin immunoprecipitation assay quantitative polymerase chain reaction showed that Itgb2 was the target gene of transcription factor Ets1. ETS1 knockdown in rat mesangial cells decreased integrin subunit beta 2 expression. Conclusion: We found that EST1 functioned as an important transcription factor in diabetic nephropathy development through the promotion of integrin subunit beta 2 expression. EST1 might be a drug target for diabetic nephropathy treatment. Abstract : We have identified candidate differentially expressed genes and pathways by bioinformatics analysis in diabetic nephropathy, which improves our understanding of the cause and potential molecular events of diabetic nephropathy. We found that E26 transformation‐specific‐1 functioned as an important transcription factor in diabetic nephropathy development through the promotion of integrin subunit beta 2 expression.